Air-drying of soil samples – A crucial step in the determination of leachable concentrations of per- and polyfluoroalkyl substances. (April 2021) - Lange, Frank Thomas; Scheurer, Marco; Bierreth, Christian; Borho, Werner; Seeger, Ann-Kathrin; Dreher, Peter; Nöltner, Thomas
Abstract: Batch leaching tests at a liquid to solid ratio of 2 L/kg are a valuable tool for the assessment of low PFAS levels in soils. Data from different monitoring programs comprising samples without known local source of PFAS contamination showed that soil-sample drying at ambient temperature or at 40 °C prior to the leaching process leads to higher PFAS leachate levels compared to non-dried samples. The effect was greater for perfluoroalkyl carboxylic acids (PFCAs) than for perfluoroalkyl sulfonic acids (PFSAs). In a controlled field study comparing field-fresh (frozen to −18 °C and thawed) samples with air-dried (room temperature) samples median levels after drying increased to 140%–470% for C4 to C10 PFCAs and to 130%–200% for C4, C6, and C8 PFSAs, respectively. Thus, using field-fresh samples for batch leaching tests might underestimate the leachable fraction of PFAA in the field, where drying and leaching periods alternate. Highlights: Leaching tests are superior to soil analysis to assess low PFAS levels. Soil sample drying significantly increases PFAS aqueous leachate concentrations. Standard batch leaching tests may largely underestimate long-term PFAS leachability.